STUDY ON FAILURE OF TRACTOR DOUBLE-CAVITY FUEL TANK BASED ON MEASURED LOAD - ZHANG ZongYang; XIE ShuangShuang; WANG Kai; BING Tao; SUN ShiTao; WANG LiTai (Jixie qiangdu)
Aiming at the problems that the failure reason of the solid partition structure inside the double-cavity fuel tank is not easy to obtain and the load is not to quantify of a tractor, a fatigue failure solution for fuel tank based on the measured load is proposed. The fracture of the sample was observed and analyzed by SEM, and the failure mode was determined to be fatigue failure. Based on the analysis of the mechanical properties of fuel , the main reason for the failure of the double-cavity tank wasthat the solid partition receives too much impact force due to the insufficient sloshing damping provided by single damping baffle. The porous damping baffle was added inside the fuel tank to reduce the impact force of fuel sloshing on the solid baffle during driving and the tank structure was optimized. Sensors were installed at key positions before and after fuel tank optimization. The strain load spectrum of solid partition plate before and after optimization of double-cavity fuel tank was compared in the test field. and the difference of strain load before and after optimization was quantified by means of amplitude, rain flow and statistical analysis of the load data. The measured load of the fuel tank before and after optimization was quantitatively analyzed, and the maximum load value decreases by more than 60% after optimization, which indicates that the damping baffle can effectively reduce the impact force of fuel on the solid partition. After optimization, there was no tank failure problem in the road test field, which indicates that the optimized strain load of the solid partition was lower than the fatigue limit of the fuel tank, and the fatigue life of the solid partition was increased. To verify that the optimized fuel tank structure meets the safety requirements, and to provide theoretical guidance and data for the subsequent optimization and the next generation of new product development.